Optimizing Hydroponics Farming: A Comprehensive Review of AI and IoT Integration for Enhanced Efficiency and Sustainability - , Jasmal Choorappulakkal, Prashant Jaglan; Shubham, Shilpa Kaushal (Archives of Current Research International, 2024)
Innovative techniques for sustainable agriculture, such as hydroponics and aeroponics, have come to light as viable answers to problems with food security. The present review delves at the ways in which Artificial Intelligence (AI) and the Internet of Things (IoT) might be combined to optimize farming methods, with an emphasis on improving sustainability and efficiency. This article examines artificial intelligence's involvement in smart farming and highlights how it helps with decision-making, crop monitoring, and predictive analytics. The usefulness of IoT technologies for automated system management and real-time data collection in controlled environment agriculture is also highlighted. The research goes into additional detail on the complementary ways that AI and IoT work together to increase crop yields and resource efficiency. Furthermore, scalability, affordability, and technical knowledge constraints and opportunities are examined. The study also assesses the benefits and drawbacks of hydroponic technology, weighing its advantages for the environment against possible drawbacks like setup fees. Ultimately, the future of controlled environment agriculture is shaped by developing technologies, AI-driven model developments, and Internet of Things innovations. These are the study areas and future trends that are identified. The goal of this thorough analysis is to shed light on the state of artificial intelligence (AI) and Internet of Things (IoT) applications for hydroponic and aeroponic farming.